Effect of Water-Deficit Stress on the Selected Landraces and Improved Varieties of Rice (Oryza sativa L.) in Nepal - Baniya, Seema; Pokhrel, Chandra Prasad; Thapa, Lal Bahadur (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Water stress is one of the adverse factors affecting growth, development and productivity of rice. It is crucial to explore the drought tolerant rice varieties and improve their quality for sustainable production for droughtprone environments. The aim of this study was to know the ability of selected landraces (Aapjhutta, Kartika, Aanadi and Jhapamansuli) and improved varieties (Khumal-8, Khumal-10, Khumal-11 and Chainung-242) of rice to tolerate water-deficit stress in Nepal. The rice plants were grown in polyethylene pots. The pots were watered for the first two days of seedling transplantation and then watering was stopped. Survival and survival probability of seedlings were calculated. In addition, the concentration of an osmolyte (proline) was estimated after complete death of the plants in each variety. Two rice varieties, Jhapamansuli and Aapjhutta showed the highest seedling survival under water-deficit stress than the improved and other rice varieties. Results indicated that these two varieties have the ability to survive better than others under the stress by accumulating a high amount of proline as a compatible solute. Thus, these varieties can be preserved and utilized for breeding activities to develop drought tolerant and high yielding varieties.